Predicting DNA sequence motifs of recombination hotspots by integrative visualization and analysis - Khil, Pavel P. (2013)
Meiotic recombination hotspots play important roles in life sciences, but the regulatory mechanism remain unclear. To predict DNA sequence motifs that regulate recombination hotspots, we designed an open source software tool called “LDsplit” that detects SNPs (single nucleotide polymorphisms) associated with meiotic recombination hotspots. The association is measured by the difference of historical recombination rates at a hotspot between two sub-populations with different alleles of a candidate SNP. Providing userfriendly graphic interface and integrative visualization, LDsplit provides insight into the relation of recombination hotspots with proximal DNA sequence patterns.